Exercise therapy for spondyloarthritis: a systematic review - Wilson, Fiona; O'Shea, Finbar (My University, 2014)
t o evaluate the effects of therapeutic exercise on pain, stiffness, quality of life, physical function, dis- ease activity, health-related fitness and cardiovascular risk factors in adults with spondyloarthritis (SpA). electronic databases (cochrane central Register of controlled trials, eMBASe, MeDlINe/PubMed, PeDro, AMeD, cINAHl) were systematically searched from inception to October 2013 using medical subject headings and keywords. this was supplemented by searching conference abstracts and a hand search of reference lists of included studies. Ran- domised and quasi-randomised studies of adults with SpA in which at least one of the comparison groups received an exercise intervention were included. Outcomes of interest were pain, stiffness, quality of life, physical function and disease activity. Secondary outcomes were health-related fitness and cardiovascular risk factors. two reviewers inde- pendently screened studies for inclusion. Methodological quality was assessed by two reviewers using the cochrane risk of bias tool and the PeDro scale. twenty-four studies, involving 1,498 participants, were included. Meta-analyses were not undertaken due to clinical heterogeneity, and this review focuses on qualitative synthesis. Moderate evidence supports exercise interventions in improving physical function, disease activity and chest expansion compared to controls; there is low-level evidence of improved pain, stiffness, spinal mobility and cardiorespiratory function. Supervised group exercise yields better outcomes than unsupervised home exercise. the addition of aerobic com- ponents to flexibility programmes improves cardiorespi- ratory outcomes, but not cardiovascular risk factors. the most effective exercise protocol remains unclear. current evidence suggests that therapeutic exercises are beneficial for adults with ankylosing spondylitis; effects on other SpA subtypes are unknown
PUBLISHED
Keywords: Ankylosing spondylitis; Immunology, Inflammation & Infection; ANKYLOSING-SPONDYLITIS; PHYSICAL ACTIVITY; Rheumatology and rheumatological disorders